Breaking Barriers: Identifying and Overcoming Social Exclusion in Voluntary Sports Clubs for Older Adults Affected by Poverty - Oettle Lukas (Physical Culture and Sport: Studies and Research, 2025)
Poverty and social exclusion are intricately linked and can lead to profound health and social repercussions. Participation in voluntary sport clubs (VSCs) could help counteract these consequences, but those affected by poverty are underrepresented.